2020
DOI: 10.3390/su12156155
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Knowledge-Based Network Structure Hole on Enterprise Innovation Performance: The Threshold Effect of R&D Investment Intensity

Abstract: The purpose of innovation is to consume fewer natural resources in order to create sustainable performance; therefore, innovation can ease the pressure of the ecological load and promote the sustainable development of the economy. Taking the 269 enterprises listed on the main board of the electronic information industry from 2010 to 2019 as samples, using the threshold panel data model, the nonlinear relationship between the knowledge-based network structure hole and the short-term and long-term innovation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…But this kind of knowledge is usually hard coded, tacit, complex and socially embedded, and in order to acquire technology overflow and cultivate technology learning ability, enterprises need to establish a strong internal knowledge base to identify and judge this knowledge [ 68 , 69 ], by combining differentiation of international advanced knowledge to make up for their own weak link of knowledge innovation [ 70 , 71 ]. Therefore, emerging market enterprises tend to form close R&D alliances with domestic suppliers, distributors, customers and even competitors to absorb, integrate and transform the knowledge acquired from R&D internationalization [ 72 , 73 ], so as to enhance their own R&D strengths. Due to the unity of cultural practices, jet lag and language barriers, trust and loyalty between domestic technology alliance members is stronger, and the members can directly, through face-to-face communication, meetings and other communication forms, obtain knowledge.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…But this kind of knowledge is usually hard coded, tacit, complex and socially embedded, and in order to acquire technology overflow and cultivate technology learning ability, enterprises need to establish a strong internal knowledge base to identify and judge this knowledge [ 68 , 69 ], by combining differentiation of international advanced knowledge to make up for their own weak link of knowledge innovation [ 70 , 71 ]. Therefore, emerging market enterprises tend to form close R&D alliances with domestic suppliers, distributors, customers and even competitors to absorb, integrate and transform the knowledge acquired from R&D internationalization [ 72 , 73 ], so as to enhance their own R&D strengths. Due to the unity of cultural practices, jet lag and language barriers, trust and loyalty between domestic technology alliance members is stronger, and the members can directly, through face-to-face communication, meetings and other communication forms, obtain knowledge.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Due to the similarity of the economic environment and institutional system faced by domestic technology alliance enterprises, compared with overseas technology alliances, it is easier for domestic technology alliance enterprises to make use of scopes of economy to obtain profits. Enterprises usually set up R&D institutions within the geographical scope of universities, research institutes, domestic government institutions, suppliers and other institutions, so as to gain diversified knowledge and technology spillover in different fields [ 76 , 77 ], through common technology platforms and proprietary equipment to synergy with the domestic technology alliances [ 78 ], so as to obtain the knowledge and technical supplement to promote innovation [ 73 ]. In view of this, this paper proposes:…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…In important studies, the rate of business activity is considered to be one of the key determinants of economic development (Urbano et al, 2016;Remeikiene et al, 2020). The systematic review of empirical research on the impact of entrepreneurship on economic, social and environmental well-being is summarised in several studies (Block et al, 2019;Halasi et al, 2019;Hao et al, 2020). Some authors have found that entrepreneurial activity may vary according to the country's level of economic development.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In 2018, John R. Bolton, then Assistant to the President for National Security Affairs of the United States, gave a strong speech on African issues, criticizing China and Russia for their corrupt business practices in Africa (https://www.sohu.com/a/281853086_116897, accessed on 10 February 2021). Some scholars examined the correlation between the corruption level and Chinese investment preferences based on the data of Chinese companies investing in Asian and African areas with extremely high corruption levels, in order to prove that Chinese investors may actually welcome a highly corrupt business environment [63,64]. Isaksson and Kotsadam [57] adopted measurement methods to verify that China's aid to Africa fuels local corruption.…”
Section: Diffusion Of Bad Governance-diffusion Of Corruptionmentioning
confidence: 99%